2017
DOI: 10.1093/mnras/stx1685
|View full text |Cite
|
Sign up to set email alerts
|

Shutting down or powering up a (U)LIRG? Merger components in distinctly different evolutionary states in IRAS 19115−2124 (the Bird)

Abstract: We present new SINFONI near-infrared integral field unit (IFU) spectroscopy and SALT optical long-slit spectroscopy characterising the history of a nearby merging luminous infrared galaxy, dubbed the Bird (IRAS19115-2114). The NIR line-ratio maps of the IFU data-cubes and stellar population fitting of the SALT spectra now allow dating of the star formation (SF) over the triple system uncovered from our previous adaptive optics data. The distinct components separate very clearly in a line-ratio diagnostic diagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…We are not sensitive to any merging populations which are in their final stages, or, as some studies have observed, multi-nucleus systems at sub-arcsecond resolutions (e.g., Smail et al 2003;Alaghband-Zadeh et al 2012;Menéndez-Delmestre et al 2013). Indeed, a recent study of a local Ultra-Luminous Infrared Galaxy (ULIRG 15 ) triple system found that if it were to be found at high redshift, it would likely be misidentified as a clumpy galaxy or a small group (Väisänen et al 2017). However, our results hold for any well resolved components at arcsecond scales, such as those found by Karim et al (2013), where the typical separation is ∼ 6 arcsec.…”
Section: Discussionmentioning
confidence: 99%
“…We are not sensitive to any merging populations which are in their final stages, or, as some studies have observed, multi-nucleus systems at sub-arcsecond resolutions (e.g., Smail et al 2003;Alaghband-Zadeh et al 2012;Menéndez-Delmestre et al 2013). Indeed, a recent study of a local Ultra-Luminous Infrared Galaxy (ULIRG 15 ) triple system found that if it were to be found at high redshift, it would likely be misidentified as a clumpy galaxy or a small group (Väisänen et al 2017). However, our results hold for any well resolved components at arcsecond scales, such as those found by Karim et al (2013), where the typical separation is ∼ 6 arcsec.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Fig. 1, see Väisänen et al 2008Väisänen et al , 2017. The emitting regions in LIRGs are distributed across the galaxies covering regions with sizes between 1 kpc to approximately 10-20 kpc.…”
Section: Hydrogen Recombination Linesmentioning
confidence: 96%
“…1 illustrates the power of such spatially resolved observations. The images show details of the nearby LIRG IRAS 19115-2124 with log(L IR /L ) = 11.91 (for D L = 206 Mpc), a triple merger whose components show signs of multiple stages of galaxy evolution, including the triggering and quenching of SF, and the appearance of AGN activity (Väisänen et al 2008(Väisänen et al , 2017. The authors noted that, if observed at high-z, the lack of the spatial information would have made this system look just like another clumpy starburst, potentially leading to a substantial misinterpretation of the ongoing processes therein.…”
mentioning
confidence: 99%
“…Based on the position on the BPT diagram, the presence of an AGN cannot be confirmed nor ruled out. Larkin et al (1998) suggested the line ratios [Fe II]/Pa β and H 2 /Br γ as a diagnostic of whether galaxies are LINERs or Seyfert type AGNs using the near-IR spectral region, and this idea was further developed in Rodríguez-Ardila et al (2004), Rodríguez-Ardila, Riffel & Pastoriza (2005), Riffel et al (2013), and Väisänen et al (2017). Riffel et al (2013) find 0.6 < [Fe II] / Pa β < 2 and 0.4 < H 2 / Brγ < 6 as determining criteria for an AGN classification based on a large sample of objects, with lower values for these ratios indicating a star-forming galaxy (SFG).…”
Section: Optical and Near-ir Spectral Analysismentioning
confidence: 99%